The Influence of Contemporary Figurative Painting in China (1989-2005): A Case Study of Contemporary Figurative Paintings by 5 influential artists - Zhang, Shuwen; Hassan , Sharmiza Abu; Liza Marziana Mohammad Noh, (Advances in Humanities and Contemporary Studies, 2025)
The research explored and analysed the art expressions based on satire, meddling, and overall cynicism about the changing systems of the economy due to the effect of globalisation in China. This paper created a thematic division and comparative analysis of the selected paintings by the five artists in contemporary China between the years 1989 to 2005 using qualitative case study method. The economic dynamism and effect of globalisation were effective in the mainstream cultural and social change. The study employed the theory of semiotics to understand symbolic representation, the use of colours, forms, and composition, and changing composition techniques in the development process of Chinese contemporary figurative paintings. This way, the study created a significant position in analysing the globalisation effect on cultural expression through figurative Chinese art using selected case studies of five influential artists, Yue Minjun, Fang Lijun, Zeng Fanzhi, Wang Guangyi, and Zhang Xiaogang.